An Unusual Case of Migraine Preconception and Severe Postpartum Headache and Intracranial Hemorrhage - Nighat Fatima; Ayesha Salman; Lama Khalid Hamza; Tooba Shakeel (Dubai Medical Journal)
Migraine affects many women in their childbearing years and gets worse during pregnancy, probably due to fluctuations in reproductive hormones. Similar changes in maternal physiology due to pregnancy increase the susceptibility toward secondary headache disorders and can cause the return of migraines in the postpartum period. Increased occurrence of headaches is also associated with the administration of epidural anesthesia, which decreases cerebrospinal fluid pressure. However, the less common causes such as secondary headache disorders related to cerebrovascular disorders and hypertension should be considered for differential diagnosis in this group of patients. In this case report, we discuss the case history of a 36-year-old woman, with a past history of migraine without aura, who presented at 1 week postpartum with headache, confusion, dizziness, right-sided weakness, and urinary incontinence. Brain imaging studies revealed global hypoxic ischemic injury to the brain. This case report discusses her presentation, investigations, management, and etiology of migraine, leading to stroke and death postpartum.